Outcome of Total Arterial Coronary Artery Bypass Grafting: Our Initial Experience - Bhattarai, Anil; Khakural, Prabhat; Shrestha, Yuna (Nepal Journal of Health Sciences, 2024)
Introduction: Total arterial coronary artery bypass grafting has better outcome than the conventional operative technique, in which vein grafts are also used. Objective: The objective of the study was to describe the patient demographics, coronary artery involvement, arterial conduit used and early outcome of patients undergoing total arterial coronary artery bypass grafting. Methods: A retrospective, descriptive study was conducted at the Manmohan Cardiothoracic Vascular and Transplant Centre, Institute of Medicine, Kathmandu, Nepal, including all the patients who underwent total arterial coronary artery bypass grafting from November, 2023 to November 2024. Hospital medical records were used to review the demographics, perioperative variables and outcome parameters. Descriptive statistics was used to analyze the data. Results: Twenty patients underwent total arterial coronary artery bypass grafting. The mean age of the patients was 50.20 ± 11.76 years. Males were more commonly affected. Ten (50%) patients had double vessel disease. Hypertension was seen in 10 (50%) patients. Aortic cross clamp time was 51.22 ± 26.81 minutes and cardiopulmonary bypass time was 81.75 ± 26.93 minutes. Left internal mammary artery and radial artery were used in 11(55%) patients, bilateral mammary and radial arteries were used in 5(25%) patients. The mean duration of stay in intensive care unit and hospital stay were 4.85± 3.70 and 11.90 ± 6.63 days, respectively. There were two mortalities due to ventricular fibrillation. Conclusion: Total arterial coronary artery bypass grafting seems feasible and safe in our setting. But a larger comparative study is essential to infer the findings statistically.